Water environment '96 supply and demand - a fragile balance : 27-28 March 1996. (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint conference with CIWEM held in March 1996.